Influence of the Type and Thickness of Cervical Margins on the Strength of Posterior Monolithic Zirconia Crowns: A Review - Haddad, Camille; Azzi, Kathy (European Journal of General Dentistry, 2022)
The aim of this research is to review the literature for the influence of the thickness and shape of cervicalmargins on the strength of posterior monolithic zirconia crowns. Studies to assess the fracture resistance of monolithic zirconia crowns with different types of cervical margins, published from 2014 to 2020, were searched using the electronic database PubMed and Google Scholar using the following keywords: “monolithic zirconia,” “translucent,” “shoulderless,” and “margin preparation design.” Analysis of studies has shown that overall the design of the margin would have a significant effect on the strength of these crowns. Monolithic zirconia crowns with a knife-edge margin have shown a breaking load higher than the maximum chewing force of humans. It would be safe to suggest the utilization of posteriormonolithic zirconia crowns with vertical preparation. As the new translucent monolithic zirconia crowns are recent, further studies would be needed to guide the selection of the appropriate minimum thickness of the knife-edge margin to meet the clinical guidelines for their use.
Keywords: margin preparation design; monolithic zirconia; shoulderless; translucent